2015
DOI: 10.4172/2472-1786.100007
|View full text |Cite
|
Sign up to set email alerts
|

Digital Personal Stories: A Case Study of Two African Adolescents, with Severe Learning and Communication Disabilities

Abstract: often too loud, too big or too heavy for inclusion in standard SEN classroom, iPads do not embody these terms [2]. Indeed, people with disabilities note that iPads may represent a shift in the "deficit discourse" [3], according to which mobile technologies can be used seamlessly and without disruption in everyday activities, including learning in the classroom. Thus, increasingly, educators are curious and keen to understand iPads' learning potential and appropriateness for all students [4]. The notion that iP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Similar motivational benefits using a story creation app (“Our Story”) have been reported for children with language and communication difficulties (Kucirkova et al, 2014b; Critten and Kucirkova, 2015). Thus, personalization could be usefully exploited to facilitate engagement.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar motivational benefits using a story creation app (“Our Story”) have been reported for children with language and communication difficulties (Kucirkova et al, 2014b; Critten and Kucirkova, 2015). Thus, personalization could be usefully exploited to facilitate engagement.…”
Section: Introductionsupporting
confidence: 53%
“…Furthermore, in a naturalistic study of TD children's use of different educational apps, Kucirkova et al ( 2014a ) found that those that allowed personalization by adding photographs, audio, and text comments to create a narrative promoted greater engagement with the task. Similar motivational benefits using a story creation app (“Our Story”) have been reported for children with language and communication difficulties (Kucirkova et al, 2014b ; Critten and Kucirkova, 2015 ). Thus, personalization could be usefully exploited to facilitate engagement.…”
Section: Introductionsupporting
confidence: 53%
“…We chose to use Our Story for this study because of our familiarity with the app through previous projects (see e.g. Critten & Kucirkova, 2015; Kucirkova, Messer, Critten, & Harwood, 2014), and practical reasons such as access to the app developers in case of problems with its technical design and the app’s free availability on the Apple and Google Play stores. The key features of Our Story relevant for this study are its open-ended design (users can create any digital stories with no restriction on the number of pictures, length of audio- or video-recordings); possibility to share the final story in multiple ways (in the current version of Our Story, finished stories can be printed out in three formats or shared with others via dropbox or email by selecting the ‘share’ feature and inserting the recipient’s details).…”
Section: The Our Story App and Personalised Multimedia Storiesmentioning
confidence: 99%
“…Although pre‐K students' personal books need to be created or cocreated by a teacher and/or parent, for older students, personal books can be created by the students themselves. In a series of studies with students with special educational needs (Critten & Kucirkova, ; Flewitt, Kucirkova, & Messer, ; Kucirkova, Messer, Critten, & Harwood, ), we documented the value of self‐made digital personal books for students' confidence, communication with others, and inclusion in the classroom.…”
Section: Digital Personal Books Bridging Home and Schoolmentioning
confidence: 99%
“…In Critten and Kucirkova (), we observed the use of Our Story with two African adolescents who immigrated to the United Kingdom and attended a special needs school. The boys had profound language and learning difficulties and were often reprimanded for disrupting the classroom dynamics.…”
Section: Digital Personal Books Bridging Home and Schoolmentioning
confidence: 99%